2021
DOI: 10.1371/journal.pone.0248958
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and association with delivery outcome of curable sexually transmitted infections among pregnant women in Southern Ethiopia

Abstract: Introduction Curable sexually transmitted infections (STIs) such as infection with Chlamydia trachomatis (C. trachomatis), Neisseria gonorrhoeae (N. gonorrhoeae), and Trichomonas vaginalis (T. vaginalis) can lead to adverse pregnancy and birth outcome. There are limited data on the prevalence and correlate of STI in Ethiopia, yet pregnant women are not screened for curable STI. Hence in this study, the prevalence of STIs and associated risk factors were assessed. Methodology A cross- sectional study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
(52 reference statements)
3
11
2
Order By: Relevance
“…These are Oromia, [21][22][23][24] Amhara, 19,25,26 Addis Ababa, 20,27 and South Nation, Nationalities and People (SNNP). 28 These studies used different diagnostic methods that include wet-mount microscopy, Giemsa staining, culture, and trichomonas rapid diagnostic test to detect T. vaginalis (Table1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…These are Oromia, [21][22][23][24] Amhara, 19,25,26 Addis Ababa, 20,27 and South Nation, Nationalities and People (SNNP). 28 These studies used different diagnostic methods that include wet-mount microscopy, Giemsa staining, culture, and trichomonas rapid diagnostic test to detect T. vaginalis (Table1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…28,29 As it is known, 90% of trichomoniasis are from resource-limited settings, specifically sub-Saharan countries. 30 Although population-based studies were lacking in Ethiopia, different studies reported different prevalences of T. vaginalis; 5.3% from Asella Teaching Hospital, central Ethiopia, 31 3.1% from Hawassa comprehensive and specialized hospital, Southern Ethiopia, 32 4.9% from Jimma University Specialized Hospital, Southwest Ethiopia 33 and 2.1% from Felege Hiwot referral Hospital, Ethiopia: a cross sectional study. 13 Though the association of vaginitis with genital tract infection is a major problem globally, several studies on https://doi.org/10.2147/IDR.S337205…”
Section: Introductionmentioning
confidence: 99%
“…As such women having history of termination of pregnancy have higher odds of self-reported STIs than their counterparts. This is supported by the study in Ethiopia [35]. This might be due to those women who had history of termination of pregnancy would have better access to reproductive health care service, sexual, and better understanding of symptoms of STIs.…”
Section: Discussionmentioning
confidence: 76%